The Role of 3D Printing in Customizing Dental Prosthetics and Orthodontic Appliances - Abedi Diznab, Fatemeh; Ghazi Oskouei, Hooman; Dehghan, Faeze; Dehghan, Mohamad; Golrokhian, Mohammad; Rafighi, Ali; Shenasa, Naghmeh (Galen Medical Journal, 2024)
Abstract 3D printing technology has introduced significant advancements in dentistry, particularly in the customization of dental prosthetics and orthodontic appliances. By enabling precise, patient-specific designs, 3D printing enhances both the fit and comfort of dental devices, improving patient outcomes and satisfaction. This technology offers notable efficiencies over traditional manufacturing methods, reducing production times and costs while supporting seamless digital workflows in clinical practice. Recent advancements in biocompatible materials and digital integration have expanded the application of 3D printing to a range of dental devices, from crowns and bridges to clear aligners and retainers. However, challenges remain, including material limitations, regulatory hurdles, and technical constraints that can impact adoption, particularly in smaller clinics. Future research aims to address these challenges by exploring new materials, incorporating artificial intelligence for optimized design, and enhancing environmental sustainability through waste reduction. The ongoing evolution of 3D printing in dentistry promises to further personalize and streamline dental care, paving the way for a more patient-centered, efficient, and accessible approach in modern dental practices.